The Validity of Astronomical Calculation in Determining the Lunar Month - Umpa, Aleem Morad (JPAIR Multidisciplinary Research, 2018)
Astronomical calculations, in the view of the majority of jurists, rest on mere assumptions and are hypothetical in nature. Therefore, significant acts of worship such as the beginning and end of the month of Ramadhan cannot be determined by calculations. The study aimed to validate the astronomical calculation in determining the beginning of new lunar month in connection with Islamic acts of worship. The study utilized descriptive and qualitative research method through in-depth study of printed and internet sources. Results showed that sighting and calculations are complementary and both are needed. Calculations to negate false sighting is used, but not to completely replace sighting. Thus, if the calculations say with certainty that Hilal cannot be visible, then we should reject or negate the false sighting and reduce errors. Since astronomical calculations, especially on the birth of new Moon, are absolutely precise, the claim that a consensus exists among all the Muslim jurists regarding absolute mistrust of astronomical calculations, in all forms and ways, related to the beginning and ending of the Islamic months are unfounded, though the majority adopted that opinion because of the uncertainties connected with calculations in their times. Although calculations alone cannot be used to determine the start of the new lunar month, this does not mean that we should disregard it.
Keywords: Astronomical calculation; moon sighting; lunar month; qualitative study; Islamic communities